2007
DOI: 10.1359/jbmr.060914
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA-Dependent Protein Kinase Is Involved in 2-Methoxyestradiol—Mediated Cell Death of Osteosarcoma Cells

Abstract: We studied the involvement of interferon-regulated, PKR on 2-ME-mediated actions in human osteosarcoma cells. Our results show that PKR is activated by 2-ME treatment and is necessary for 2-MEmediated induction of osteosarcoma cell death.Introduction: Osteosarcoma is the most common primary bone tumor and most frequently develops during adolescence. 2-Methoxyestradiol (2-ME), a metabolite of 17␤-estradiol, induces interferon gene expression and apoptosis in human osteosarcoma cells. In this report, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…In regard to hypoxia, 2-methoxyestradiol has been shown to act as an inhibitor of tumor growth and vascularization through its ability to downregulate Stat3 and HIF-1α (44,45). Interestingly, 2-methoxyestradiol is a potent inducer of apoptosis in tumor cells by activating PKR (46). We observed that 2-methoxyestradiol treatment of hypoxic MEFs resulted in the downregulation of HIF-1α in a manner that was dependent on PKR ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 79%
“…In regard to hypoxia, 2-methoxyestradiol has been shown to act as an inhibitor of tumor growth and vascularization through its ability to downregulate Stat3 and HIF-1α (44,45). Interestingly, 2-methoxyestradiol is a potent inducer of apoptosis in tumor cells by activating PKR (46). We observed that 2-methoxyestradiol treatment of hypoxic MEFs resulted in the downregulation of HIF-1α in a manner that was dependent on PKR ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 79%
“…We have previously demonstrated that PKR plays a role in 2-ME-mediated cell cycle arrest and apoptosis in osteosarcoma cells [24], [25]. Osteosarcoma cells expressing transdominant mutant PKR is resistant to anti-cellular and anti-tumor effects of 2-ME [24]. In this report, we show that 2-ME-mediated autophagosome formation and the conversion of LC3-I to LC3-II are inhibited in cells that express dominant negative mutant PKR protein.…”
Section: Discussionmentioning
confidence: 50%
“…2-ME treatment induces PKR expression and PKR activity in osteosarcoma cells [24]. To determine whether PKR is required for 2-ME-mediated autophagic flux, we have investigated the effect of 2-ME on autophagosome formation and LC3-I to LC3-II conversion, in osteosarcoma cells that have been stably-transfected with trans- dominant mutant PKR cDNAs and are defective for PKR activity and resistant to 2-ME-mediated anti-proliferative effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations